Effect of age and physiological reproductive status on the fibre diameter profile in Huacaya alpacas - Olarte Daza, Ceferino Uberto (2022)
The study aimed to determine the effect of age and reproductive status on the fibre profile in female Huacaya alpacas from Puno, Peru. Age (young, younger adult, older adult, and old) and reproductive status (pregnant lactating, non-pregnant lactating, pregnant without calf at foot, and non-pregnant without calf at foot) were considered. After one year of fibre growth, samples were taken from the middle rib (5 g) and analysed with the optical fibre diameter analyser (OFDA 2000) equipment. The data were fitted to a cubic linear regression and analysed under a 4x4 factorial in a completely randomized design. Means were compared using the Duncan's multiple test. Age and reproductive status interact in the presentation of the fibre diameter profile, as well as the minimum initial diameter and the maximum diameter, where young and pregnant lactating present the smallest diameter (p<0.05). The age factor had a significant effect on the final minimum diameter and the initial rate of change, while age and reproductive status influenced the final rate of change of the fibre profile. In conclusion, the fibre diameter profile in female Huacaya alpacas shows a characteristic pattern in diameter changes over the course of the year, which coincides with the rainy season when there are important changes in nutrient availability in the Andean prairie.